Postcards From Camp : A Postal Story - Taback, Simms (New York : Nancy Paulsen Books, 2011)
Follows Michael's summer at sleep-away camp through a series of postcards sent between him and his father.
Keywords: Postcards -- Fiction; Camps -- Fiction; Toy and movable books